2021
DOI: 10.1007/s12529-021-09964-2
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation Strategies Predict PTSS During the COVID-19 Pandemic in an American Indian Population

Abstract: Background Poor emotion regulation is associated with post-traumatic stress symptoms (PTSS). However, limited prospective research prevents any directional conclusions. No known studies have assessed emotion regulation with PTSS in American Indians, a high-risk population for poor mental health outcomes. The present prospective study explored whether emotion regulation strategies (cognitive reappraisal, expressive suppression) predicted later PTSS related to the COVID-19 global pandemic in a solel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
3
19
0
Order By: Relevance
“…The results showed that students who had COVID-19 symptoms, had a greater prevalence of PTSD symptoms and DERS. The current study adds to the body of knowledge suggesting a link between emotion regulation difficulties and PTSD (Weiss et al, 2012;Ehring & Quack, 2010;Tyra et al, 2021). Students who exposed to trauma reported significantly higher levels of overall difficulty with emotion regulation, as well as difficulties controlling impulsive behaviors when distressed, difficulties engaging in goal-directed behavior when upset, limited access to effective emotion regulation strategies, difficulties accepting emotions, difficulties having a clear understanding of their emotions, and difficulties with self-awareness.…”
Section: Discussionmentioning
confidence: 69%
“…The results showed that students who had COVID-19 symptoms, had a greater prevalence of PTSD symptoms and DERS. The current study adds to the body of knowledge suggesting a link between emotion regulation difficulties and PTSD (Weiss et al, 2012;Ehring & Quack, 2010;Tyra et al, 2021). Students who exposed to trauma reported significantly higher levels of overall difficulty with emotion regulation, as well as difficulties controlling impulsive behaviors when distressed, difficulties engaging in goal-directed behavior when upset, limited access to effective emotion regulation strategies, difficulties accepting emotions, difficulties having a clear understanding of their emotions, and difficulties with self-awareness.…”
Section: Discussionmentioning
confidence: 69%
“…Compared to the general United States population, AIs experience disproportionately high rates of childhood trauma and adversity (Beals et al, 2013; Manson et al, 2005). While emotion regulation strategy use is implicated in the relationship between adversity and mental health in other ethnic minority groups, research is limited in AI populations (Carter et al, 2020; Tyra et al, 2021). Additionally, evidence suggests that culture plays a role in how we experience and express emotions.…”
Section: Emotion Regulation Strategies Psychological Stress and Indic...mentioning
confidence: 99%
“…Additionally, difficulties with ER associated with alterations in frontoamygdala circuitry following ELS may have particularly important implications during times of heightened stress. The regulatory processes (e.g., reappraisal, suppression) by which individuals initiate, maintain, and modify their own reactions to the negative emotions that are often engendered during experiences of heightened stress may influence subsequent psychological states ( 35 , 36 ). Recent work has shown that disruptions in ER processes have been associated with increased risk for mental health issues during the COVID-19 pandemic ( 35 , 37 , 38 ).…”
Section: Introductionmentioning
confidence: 99%
“…The regulatory processes (e.g., reappraisal, suppression) by which individuals initiate, maintain, and modify their own reactions to the negative emotions that are often engendered during experiences of heightened stress may influence subsequent psychological states ( 35 , 36 ). Recent work has shown that disruptions in ER processes have been associated with increased risk for mental health issues during the COVID-19 pandemic ( 35 , 37 , 38 ). For example, Tyra and colleagues (2021) demonstrated that greater use of reappraisal and lesser use of suppression was associated with reduced risk for developing stress-related symptomatology during the COVID-19 pandemic ( 35 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation